Profil Destinasi Wisata Alam Sumber Manis Sebagai Media Promosi Wisata Di Banyuwangi - Mulyadi, Adi; Abdurrahman; Indari (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2023)
This paper discusses the profile of the Sumber Manis Tourism destination. The destination profiles are used to promote tourism for local, domestic and foreign tourists. The manager of Alam Sumber Tourism is experiencing problems regarding the use of social media, and the potential for tourism to introduce its destinations. So that students and lecturers propose to collaborate with PT and Tourism Destinations in Banyuwangi in creating social media accounts and making profile books for promotion for visiting tourists. The method is carried out by survey, socialization and mentoring for 45 days. The results show that the impact of social media can increase visitors by 10% on Saturdays and Sundays and tourists understand tourism potential with profile books.